Types of materials for frontalis sling surgery for congenital ptosis - Andersen, James (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the comparative effectiveness and safety of various materials used in frontalis sling surgery for congenital ptosis.